Key Strata Inducing Dynamic Disasters Based on Energy Condition: Criterion and Application. (20th February 2021) - Xu, Chao; Yang, Gang; Sun, Haoshi; Qin, Liangliang; Wang, Kai; Ren, Bo; Wen, Zhijie
Abstract : The thick and hard rock strata (THRS) exist widely in coal measure strata, which control the movements of overlying rock strata in stopes. When THRS break, great energy is released, which could aggravate the risks of coal and gas outburst, rock burst, and other dynamic disasters. Therefore, the foundation and key of preventing dynamic disasters are to distinguish the THRS that could induce coal-rock dynamic disasters and to analyze the laws of rock stratum breaking and energy releasing. The paper proposed the theoretical calculation methods of the energy accumulation and attenuation of rock breaking which is greatly affected by the hanging length of rock strata and the spreading distance. One or more roof strata that play a leading role in inducing dynamic disasters of the underlying coal mass are defined as the key disaster-inducing strata (KDIS). The disaster-inducing coefficient (DIC) is defined and used as the criterion of KDIS. The greater the source energy, the shorter the spreading distance, and the smaller the attenuation coefficient are, the easier the roof strata are to become KDIS. The disaster-inducing ability of the main THRS was analyzed, and the igneous sill was judged as KDIS, taking the Yangliu Coal Mine as project background. The breaking laws of the igneous sill were obtained by the methods of UDEC numerical simulation and microseismic monitoring, which verified the criterion of KDIS.